The Impact of Using Cell Phones on the Pronunciation of English Consonant Clusters among Saudi Female Secondary School Students - Alhomaidhi, Shrowg (International Journal of Interactive Mobile Technologies (iJIM), 2021)
This research attempts to find out the impact of using cellphones on the students’ pronunciation with an emphasis on consonant clusters. The sample of the study was 40 female secondary school students divided into two groups control and experimental. The study attempted to answer one question: Will the use of pronunciation videos on cell phones help to improve Saudi female secondary students' pronunciation of English consonant clusters occurring in the onset position? To achieve this, the researcher conducted a pre-test and a post-test to test students’ pronunciation of selected vocabulary from the English Inventory of consonant clusters. After the pre-test, the experimental group used video to practice these sounds while the control group practiced that in traditional classes. The findings showed that both groups improved. However, the excremental group, having utilised cell phone videos, made significant improvement by 7.05% in the correct production of consonant clusters.